15th International Equitation Science Conference. Bringing science to the stable (University of Guelph, 2019)
The conference took place at the University of Guelph, in Guelph, ON, Canada from August 19-21. The University of Guelph, considered Canada`s Equine University, offers unique diploma, degree, certificate and online learning opportunities specific to equine alongside undergraduate and graduate studies in animal and veterinary science. The practical day was held at the Ancaster Fairgrounds in Ancaster, ON, Canada.